Maternal depression increases infant risk of diarrhoeal illness: –a cohort study. Issue 1 (11th September 2006) - Rahman, A; Bunn, J; Lovel, H; Creed, F
Abstract : Aims: To examine the associations between postnatal depression in mothers and diarrhoeal illness in their infants in the first year of life in a low-income country. Methods: Using a prospective cohort design, 265 infants (n = 130 of mothers having a depressive episode according to the International Classification of Diseases, 10th revision, at 3 months postnatal and n = 135 of psychologically well mothers) living in rural Rawalpindi, Pakistan, were followed up for 1 year. Frequency of diarrhoeal episodes was measured fortnightly by health workers using a standard questionnaire. Results: Infants of depressed mothers had significantly more diarrhoeal episodes per year than those of controls (mean 5.5 v 4.0; 95% confidence interval (CI) 0.9 to 2.0). The relative risk of having ⩾5 diarrhoeal episodes per year in infants of depressed mothers was 2.3 (95% CI 1.6 to 3.1). The association remained significant after adjustment for other risk factors by multivariate analysis. Conclusions: Maternal depression is associated with infant diarrhoeal morbidity in a low-income community setting. It is independent of the effects of known factors such as undernutrition, socioeconomic status and parental education. Preventive child health programmes targeting mothers must consider their mental health.